Kajian Hadis Kontemporer Sarjana Amerika:Telaah Pemikiran Hadis Jonathan A.C. Brown - Arif Budiman; Sri Handayana (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
The direction of hadith studies in the contemporary era has changed. The proof, the studies presented by scholars are more varied. Not only at the level of the study of the authenticity of hadith but has gone beyond normative studies. This article aims to examine the thoughts of Jonathan A.C Brown, an expert on hadith studies from the United States and discover the nuances of contemporary hadith studies that he offers. Through qualitative analysis, this research was conducted in dialogue with the work of Jonathan A.C. Brown. The author's findings as a revaluation scholar, Brown, display two nuances in contemporary hadith studies. First, the nuances of locality - in the study of character studies and literature studies on figures and literature (al-bahṡu 'an al-a'lam wa al-musannafāt). Brown packs a canonization theory to trace the historical process of the Ṣahīḥayn text. This research model is based on the socio-cultural trends of American scholars. This synthesis contributes positively to the critical debate on Ṣahīḥayn. Second, the nuances of glocalization – on the aspect of studying the understanding of hadith (al-bahṡu 'an al-fiqh al-ḥadīṡ). In the effort to interpret the hadith, there has been an adjustment to local cultural values. This can be seen from the cases in the areas he visited and how the community or religious leaders hid a hadith. The interpretation of the hadith is directed at a substantive-philosophical understanding.